The Role of Competency-Based Performance Management in Improving Employee Performance at the Fisheries Office of Tojo Una-Una Regency - Kamumu, Irmawati S.; Indriani Ibrahim, Andi; Sipatu, Lindanur; Matalatta, Wisra; P. Adam, Rosida (JURNAL MANAJEMEN MOTIVASI, 2026)
Human resource competency is essential for improving public-sector performance. This study examines the role of competency-based performance management in enhancing employee performance at the Fisheries Department of Tojo Una-Una Regency. A descriptive qualitative approach was employed using purposive sampling, with data collected through observation, interviews, and documentation and analyzed using the Miles–Huberman–Saldaña model supported by NVivo 12. The findings indicate that technical, managerial, and social competencies, supported by appropriate placement, training, periodic evaluation, and feedback, improve work effectiveness, service quality, responsibility, and productivity. The study highlights the importance of strengthening competency standards and aligning employee placement with organizational needs.